2021
DOI: 10.18517/ijaseit.11.6.14411
|View full text |Cite
|
Sign up to set email alerts
|

A Value-Based Decision-Making Model for Selecting Sustainable Materials for Buildings

Abstract: Nowadays, the earth faces problems and challenges from different circumstances due to the dramatic rise of urban modernization. The construction industry is the most contributor to climate change. Achieving sustainability in construction is complicated, but one of the most optimal strategies is selecting building materials with a lower carbon footprint. Therefore, this research aims to investigate the criteria for sustainable materials selection, rank and prioritize sustainable criteria, and developing value-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The study has a similar result compared to the previous study that discussed the suitable material selection in buildings [48] and improves the site selection process by incorporating GIS AHP and VBD methodologies, with a specific focus on improving cost-related criteria. Decisionmakers can choose the optimum location based on specified criteria and financial considerations gleaned from GIS data much more effectively when GIS, AHP, and VBD are employed.…”
Section: Value-based Decision (Vbd)mentioning
confidence: 56%
“…The study has a similar result compared to the previous study that discussed the suitable material selection in buildings [48] and improves the site selection process by incorporating GIS AHP and VBD methodologies, with a specific focus on improving cost-related criteria. Decisionmakers can choose the optimum location based on specified criteria and financial considerations gleaned from GIS data much more effectively when GIS, AHP, and VBD are employed.…”
Section: Value-based Decision (Vbd)mentioning
confidence: 56%
“…Mayhoub et al [27] applied AHP in the development of a new evaluation framework based on four green building rating systems for selecting sustainable façade materials. A similar study was conducted by Ruslan et al [33], who used AHP and Value-based Analysis to choose the most sustainable material for façade use, between Aluminum Composite Panel (ACP) and Stainless Steel. Dinh et al [25] identified a list of 18 sustainability criteria applicable to the selection of sustainable materials in Vietnam, and used AHP to rank them based on their degree of relevance to the country's construction sector.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Despite the relevance of optimizing the construction materials selection process, currently, in practice, this is still primarily done empirically, based on the engineers' knowledge and experience, rather than numerical approaches [30][31][32]. However, when associated with the lack of experience of the responsible professional, this heuristic approach prevents the available alternatives from being objectively compared [25,33], and the lowest price ends up prevailing as the most important choice criterion. Therefore, it is essential to develop a systematic decision model that helps team members to choose the most advantageous materials, based on well-defined, sustainable, and unambiguous criteria [23,32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the 1960s, architecture students introduced this movement to solve problems formulated in project proposals. The architect's job is to be the one who best knows how to solve the problems their partners need [9]- [12]. This method was followed by famous architects [13]- [17].…”
Section: Introductionmentioning
confidence: 99%